Improved grid voltage sensorless control strategy for railway power conditioners. Issue 12 (1st December 2015) - Bozorgi, Amir Masoud; Sanatkar Chayjani, Majid; Mohammad Nejad, Reza; Monfared, Mohammad
Abstract : Rapid development of high‐speed trains confronts the power grid with serious power quality problems. In this study, to compensate power quality, an improved grid voltage sensorless control method for the railway power conditioner (RPC) is proposed. The proposed control strategy utilises a moving average filter to better detect the compensating currents and a proportional‐resonant controller to control the compensating currents. Moreover, a sensorless virtual flux method based on second order low‐pass filters is presented to replace the AC voltage sensors. Using the proposed strategy, the dynamic and steady‐state characteristic of the RPC is significantly enhanced. Through simulation tests, the effectiveness of the proposed methods is confirmed.